The Pegon Tajweed Book in Java in the 20th Century: A Study of the Book of Syifā’ al-Janān Fī Tarjamah Hidāyah al-Ṣibyān by KH. Ahmad Muthohar - Darmawan, Dwiki; Jamaluddin, Jamaluddin; Mujahidah, Affaf (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
The book Syifā al- Janān fī Tarjamah Hidāyah al-Ṣibyān is one of the important works in the discussion of the science of Tajweed, written by KH. Ahmad Muthohar. This book contains translations and explanations of the verses of poetry (nazham) of the book Hidāyah al-Ṣibyān by Sheikh Sa’id bin Sa’ad Nabhan, which are presented in Arabic Pegon format. Its concise explanation makes this book widely studied in several Islamic boarding schools in studying the science of Tajweed. This study aims to analyze the characteristics of the book Syifā al- Janān in terms of its writing structure, as well as its presentation form. This study takes data directly from its primary source, namely the book Syifā al- Janān. This study uses a qualitative descriptive method with a historical approach to examine the text and the author’s background. The results of the study show that this book has characteristics in the use of Pegon Arabic combined with a pedagogical approach in its presentation, making it a relevant reference in learning Tajweed science among Islamic boarding schools and the general public. In addition, this book also contributes to maintaining the continuity of the tradition of writing books with Pegon script in Indonesia.